1969
DOI: 10.1088/0022-3727/2/1/308
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic domain structures in 65% nickel-35% iron alloys

Abstract: The Kerr magneto-optic effect has been used to observe domain structures on rings of 65% nickel-35% iron after annealing just below the Curie point with and without an external field being present. In general the observations are consistent with the Néel-Taniguchi theory of pair orientation, but measurements of wall movement in the constant-permeability region of the hysteresis loop of the baked alloy do not agree with predictions of theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
1971
1971

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is interesting that the fitted rotational permeability for this material is not much more than twice that for the magnetically annealed specimens : in the magnetically annealed material there should be a strong tendency for domains to be oriented around the ring and so be very much less susceptible (by the rotation mechanism) to the measuring field than a random domain distribution. Jackson and Lee (1969), in a Kerr-effect study of 65-35 NiFe, found a distinct tendency for domains to be oriented around the ring even in material which had been baked in zero field. A lower proportion of 180" walls may be partly responsible for the rather lower wall susceptibility attributed to the baked than to the magnetically annealed specimens.…”
Section: Perminvar (26 %Ni-30 % F E 4 4 %Co)mentioning
confidence: 96%
“…It is interesting that the fitted rotational permeability for this material is not much more than twice that for the magnetically annealed specimens : in the magnetically annealed material there should be a strong tendency for domains to be oriented around the ring and so be very much less susceptible (by the rotation mechanism) to the measuring field than a random domain distribution. Jackson and Lee (1969), in a Kerr-effect study of 65-35 NiFe, found a distinct tendency for domains to be oriented around the ring even in material which had been baked in zero field. A lower proportion of 180" walls may be partly responsible for the rather lower wall susceptibility attributed to the baked than to the magnetically annealed specimens.…”
Section: Perminvar (26 %Ni-30 % F E 4 4 %Co)mentioning
confidence: 96%
“…It is generally assumed to be invalid at [39][40][41][42][43][44] energies lower than 100 MeV; however, there are indications that it might give good results at energies as low as 50 MeV.…”
Section: -14mentioning
confidence: 99%
“…Since A and B are antisymmetr ic states containing n nucleons it follows that <aBJBMB' aj 'm-T-ajm'rlaAJAMA =a M <aBJEME| aj,m,T-10'PJPMP> Ppp x<aPJPMplajmT'aAJAMA> (38) where the complete set of antisymme tric states composed of <aPJPMP|ajmT'aAJAMA>=nl/2<apjp;j T|}aAJA><JPJMPm|JAMA>· (39) Using results (38) and (39) in Eq. (37) and summing over projections gives:…”
mentioning
confidence: 99%
“…I t has been suggested (Kittel1949) that conventional domains do not exist in very high permeability material. Very little is known about the structure, mainly because the Bitter powder technique is not effective below anisotropy values of approximately 100 J m-3, Domain studies employing the longitudinal Kerr magneto-optic effect have been reported on various nickel-iron alloys (Jackson and Lee 1969) but not in states with vanishingly small K1. Swindell (1964) has measured the magneto-optic rotations for 77% Ni-14% Fe-5% Cu-4 % MO (by weight) material as a function of wavelength and angle of incidence.…”
Section: Introductionmentioning
confidence: 99%